2022
DOI: 10.1177/07311214221124630
|View full text |Cite
|
Sign up to set email alerts
|

Worth Less? Exploring the Effects of Subminimum Wages on Poverty among U.S. Hourly Workers

Abstract: The Fair Labor Standards Act’s minimum wage laws provide important protections for workers. However, it still permits employers to pay subminimum wages to youth under age 20, student-vocational learners, full-time students, individuals with disabilities, and tipped workers. This has important economic consequences, especially for economically vulnerable workers in the low-wage sector. Using 2009–2019 Current Population Survey–Merged Outgoing Rotation Group (CPS-MORG) data ( n = 502,976), we find that 3.7 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Previous research findings have demonstrated that raising the minimum wage can have an impact on reducing poverty (Saari et al, 2016;Syauqiah et al, 2022). On the other hand, very low wages might exacerbate poverty (Maroto & Pettinicchio, 2022). However, contrary to research by Bird & Manning (2008); Jadoon et al (2021) that poverty is unaffected by minimum wage.…”
Section: Introductionmentioning
confidence: 93%
“…Previous research findings have demonstrated that raising the minimum wage can have an impact on reducing poverty (Saari et al, 2016;Syauqiah et al, 2022). On the other hand, very low wages might exacerbate poverty (Maroto & Pettinicchio, 2022). However, contrary to research by Bird & Manning (2008); Jadoon et al (2021) that poverty is unaffected by minimum wage.…”
Section: Introductionmentioning
confidence: 93%
“…Poverty is significantly lower where wage bargaining is coordinated, centralized, and corporatist, and employment contracts are protected ( 133 , 135 – 138 , 153 ). There is also evidence that poverty is lower where minimum wages are regulated at a higher level ( 154 156 ). Recently, there has been growing interest in how institutional variation in eviction and housing laws shape poverty [e.g., ( 157 )].…”
Section: Political Explanations Of Systemically High Povertymentioning
confidence: 99%
“…For many, the New Deal era signaled a rapid entrenchment of the American welfare state beginning with the Social Security Act. In that same period, policies like the 1936 Randolph-Sheppard Act were built on the premise that people with disabilities needed special employment as they would never be hired within the regular labor market (Maroto and Pettinicchio 2022).…”
Section: Work Independence and The American Welfare Statementioning
confidence: 99%